Carbon Inequality and Allometric Uncertainty in a Micro-Scale Campus Forest in East Java, Indonesia - Citra Lesmana; Abdulkadir Rahardjanto; H. Husamah; Atok Miftachul Hudha; Tutut Indria Permana; Samsun Hadi; Ludwick Satria Romadoni (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Micro-scale urban green infrastructure provides localized ecosystem services, yet quantifying its carbon dynamics remains a methodological challenge due to satellite resolution limits and the structural assumptions of generalized models. This study evaluates carbon stock distribution across 68 individual trees within a heterogeneous 0.8-hectare institutional urban forest at a microcatchment resolution, analyzing the validity of pantropical allometry.  The stand exhibits an estimated mean carbon density of 45.38 Mg C/ha, totaling 36.34 Mg. Critically, the high coefficient of determination value of 0.9422 primarily reflects structural dependency within the allometric formulation rather than independent ecological variability. Furthermore, the Gini coefficient value of 0.654 confirms severe structural biomass asymmetry. The carbon pool is disproportionately concentrated within a limited cohort of exactly 6 Large Old Trees with a diameter exceeding 60 cm, predominantly Samanea saman. Census data reveals that the top 5% of the largest individuals manage 28.3% of the vegetative carbon, while the top 10% and top 20% control 47.3% and 66.2% of the cumulative reservoir, respectively. Within this micro-forest, inverted J-shaped diameter distributions were insufficient to ensure evenly distributed carbon storage. Consequently, urban green planning must prioritize the targeted retention of dominant biomass anchors over raw sapling quantity. Preserving these established large trees contributes significantly to institutional carbon governance, providing an empirical framework for sustainability metrics such as the UI GreenMetric.